Effect of a topical treatment with juvenile hormone analogues on dominance, ovarian development and corpora allata size in Bombus terrestris workers - Bortolotti, Laura (2020)
Juvenile hormone analogues (JHAs) are insecticides that mimic the effect of juvenile hormone (JH), one of the main regulatory hormones in insects. Negative effects of JHAs on preimaginal stages are well known, while little is known of their effects on adults. In this study we assessed the effect of three JHAs on newly emerged workers of Bombus terrestris L. kept in queenless groups. Reproductive dominance status, oocyte length and corpora allata volume were assessed 4 and 7 days after treatment. Contrary to expectations, none of the treatments had a significant stimulating effect on ovarian development in reproductive dominant workers. Conversely, most treatments caused a significant reduction in oocyte size and in corpora allata volumes of seven-day-old reproductive subordinates, indicating a feedback loop of exogenous JHAs on these glands. The study suggests that besides JH, multiple factors influence worker ovarian activity, which makes it difficult to predict the effect of the insecticides in wild colonies.